English Language Needs for Medical Students: A Link and Match of Academic and Professional Career - Wahyuni, Sri (ENGLISH FRANCA : Academic Journal of English Language and Education, 2021)
The objective of this study was to link and match the needs for an academic and professional career for medical students. The rationale is what English skills and communicative needs are learned at university should meet their needs in accomplishing their study and in pursuing their professional career. It is strongly believed that this link and match makes learning English take place. To achieve the aim of this study, descriptive analysis was used to analyze questionnaire responses. The questionnaires were distributed to 156 medical students of Baiturrahmah university who enrolled at Bahasa Inggris 6 course and had already passed Bahasa Inggris 1 to 5 courses. The finding indicated that 94,8% of medical students viewed that English was undoubtedly required for both academic and professional careers with listening and speaking skills as a priority. For medical needs, students viewed listening (82,27%) and speaking (82,21%). For professional needs, they believed listening 95.99% and speaking (85.25%) were the priority.Â  Interestingly, for academic needs, medical students needed communicative skills and strategies for reading English journal articles to finish their studies. For a professional career, participating in international seminars was in demand. By the study, it is strongly assumed that accommodating this link and match will make studying English more meaningful and beneficial.Keywords: English Language, Needs, Link, and Match.